Understanding a contextual perspectives of macroprudential policy framework - Junos, Sutina; Ma’in, Masturah; Jalil, Siti Ayu (Universiti Teknologi MARA, Kelantan, 2018)
Global financial crisis (GFC) of 2008 to 2009 has played a significant role in the collapse of the financial institutions, failure of key business, decline in consumer wealth and slump of the economy activity not only in United States (US) but in most countries in the world. A key lesson of this crisis was the importance of mitigating systemic financial risk and the need for a macroprudential approach to surveillance and regulation that can identify system-wide risks and take appropriate actions to maintain financial stability. This paper discusses the key elements of macroprudential policy framework that are implemented in many countries in order to maintain financial stability and mitigate the systemic financial risk. The discussion is based on the elements of early warning system indicators, a set of macroprudential policy instruments and an effective macroprudential institutional framework.